Evaluation of Subclinical Atherosclerosis in Patients with Psoriatic Arthritis - Enes Gül; İrfan Atik; Seda Atik (Genel Tıp Dergisi)
Background/Aims: Psoriatic arthritis with peripheral and axial involvement; It is a heterogeneous disease that can cause enthesitis, dactylitis, and nail and skin involvement. The persistence of inflammation in psoriasis leads to comorbidities such as psoriatic arthritis, cardiovascular disease, and metabolic syndrome. Our study aimed to identify subclinical atherosclerosis in psoriatic arthritis patients without a known risk factor and to prevent possible morbidity and mortality in patients. Methods: Thirty-three patients with psoriatic arthritis and twenty-five healthy control groups were included in our study. Diabetes mellitus, hypertension, coronary artery disease, diagnosis of hyperlipidemia, body mass index above 30, and smoking were determined as exclusion criteria. The age, gender, duration of the disease, medical treatment used for the disease, high-density lipoprotein, low-density lipoprotein, triglyceride, and total cholesterol values, monocyte-lymphocyte ratio, carotid intima-media thickness measurement results obtained by carotid doppler ultrasonography imaging were recorded. Results: A comparison was made between the study and control groups in terms of age, triglyceride, high-density lipoprotein, low-density lipoprotein, and monocyte-lymphocyte ratio, and no statistically significant difference was observed. Monocyte and lymphocyte levels were significantly higher in the study group (p<0.05). Carotid intima-media thickness was statistically higher in the study group and this difference was statistically significant (p<0.05). Conclusions: Patients with psoriatic arthritis have an increased risk of atherosclerosis compared to the healthy population without any risk factors. This awareness will be useful in the follow-up of patients and in taking precautions against morbidities that may develop.